Entre modas e guarânias: a produção musical de José Fortuna e seu tempo (1950-1980) - Gutemberg, Jaqueline Souza (2013)
Times study aims to understand the intricate network of relationships established between a sertanejo musical production and its times. In this sense, our interest is to analyze how this production seen as root dialogues with the new social and cultural patterns of the time, based on a national-developmentalist ideals of modern urban to Brazil between 1950 and 1980. We choose as the object of analysis the musical production of José Fortuna, composer that transited during this period between the root and the new song fads , so even unveiling a turbulent time for the genre, which followed a need for firming appreciation of the caboclas arts (as a redeemed identity) denigrating the part of modern sertanejo music. Thus, tradition and modernity opposed in country music. But while the country was changing, was modernizing, gender blended new sound elements and thematic in which the traditional and the modern was hybridizing. Visualize from this change of meaning and values of country music, a major transformation process that melded, and not without conflict, tradition and modernity.